Development, main areas, and perspectives of computer-based modeling in sport - Lames, M. (2001)
Due to the enormous progress of information technology, computer-based modeling has become an increasingly important area of research in sport science. In particular, this is the case, because information technology allows to overcome the treatment level of computational tools in favour of more sophisticated ones such as the level of concepts or the level of theory development. The first applications of computers in sport clearly made use of them as computational tools (Franks, 2000). Results of competitions had to be sorted and printed, the number of passes, assists, and scores had to be counted and plotted, or tactics were introduced by simulation on a computer screen. Frequently, researchers at this time were not aware that even the use of a computer as a simple tool could be an act of model building. For example, the widespread attempt to describe the performance of a player by the frequency of certain actions ignores both, the fact that any action in a game is part of an action chain and the well-known fact that a successful action does not only reflect the player's ability but also the skill of the opponent. A higher level of model building is achieved when concepts from information technology are adapted to problems in the area of sport. For example, the concept of information systems, which contain comprehensively all the information required in a certain area, turned out to be fruitful in the application field of training and competition. It means a complete change of perspective when you look for a solution for a task or when you try to consider a problem from the point of view of a concept in information technology. This approach turned out to be especially fruitful when questions of implementation and practical use were addressed, such as the support of teams in preparation for and during competitions (Hansen & Lames, 2001). At an other level the development of theories can be seen as a process of model building. From this view theories can be seen as abstract models, which serve to describe, explain, and control reality. In the theory of training, there exist physiological models of adaptation and information organisation, cybernetic models that focus on the action perspective, and transactional models with an intermediate position. Recent suggestions introduce a dynamic system approach to training (Mester & Perl, 2000). In this situation the principles of model building can be used as rules for a comparison of different theoretical approaches. A last perspective of model building is its potential to host interdisciplinary discussions on theoretical developments in sport science. A mutual understanding of the way models are built in different areas of sport science would help to overcome the problem of an increasing tendency towards disintegration of sport science and introduce a platform for integrating its different disciplines.